2021
DOI: 10.1177/1363460720986922
|View full text |Cite
|
Sign up to set email alerts
|

Chemsex cultures: Subcultural reproduction and queer survival

Abstract: “Chemsex” emerged in the 21st century as the gay and bisexual male practice of taking drugs during sexual encounters in order to modulate pleasures, promote endurance, and expand the temporalities of sex. Yet, while the term has come to prominence at a historical juncture when the introduction of antiretroviral drugs, locative dating apps, online pornography, and gentrification all contributed to the popularisation and mediation of the practice, the history of sex on drugs among gay men is longer than that. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 63 publications
0
16
0
1
Order By: Relevance
“…An argument which this paper will develop, building on the precious section, is the notion that "queer" and other (de) constructivist perspectives on sexual identity have been complimented by the material, technological changes of recent decades. One example of this can be seen in the expansion of amateur pornography and webcamming, as digital spaces in which non-normative desires can be explored (Florêncio, 2021;Jones, 2020). Indeed, as Weeks (2017) has noted: mediated anonymously through millions of network connections, bodily intimacy is in danger of being displaced altogether, and the distinctions between men and women, heterosexual and homosexual, adults and children, the beautiful, the ugly and the damned, may dissolve easily in the millions of possible interactions in cyberspace.…”
Section: Sex Work On Social Mediamentioning
confidence: 99%
“…An argument which this paper will develop, building on the precious section, is the notion that "queer" and other (de) constructivist perspectives on sexual identity have been complimented by the material, technological changes of recent decades. One example of this can be seen in the expansion of amateur pornography and webcamming, as digital spaces in which non-normative desires can be explored (Florêncio, 2021;Jones, 2020). Indeed, as Weeks (2017) has noted: mediated anonymously through millions of network connections, bodily intimacy is in danger of being displaced altogether, and the distinctions between men and women, heterosexual and homosexual, adults and children, the beautiful, the ugly and the damned, may dissolve easily in the millions of possible interactions in cyberspace.…”
Section: Sex Work On Social Mediamentioning
confidence: 99%
“…Among these: the impact of generational traumas (e.g., the impact of HIV epidemic, external and internalized heterosexism); technological advances and the emergence of dating mobile applications (app) and its impact in the gay hook-up culture; the appearance of new drugs with effects that were considered interesting for sexual performances ( chems a vernacular term to define GHB, methamphetamine and mephedrone) and idealized homonormativity (Bourne et al, 2014, 2015; Florêncio, 2021; Hakim, 2019; Stuart, 2019). “Like all subcultures, chemsex cultures are social worlds brought together not only through shared consumer choices, language and rituals but also through shared spaces (whether virtual or physical) and narrations about themselves” (Florêncio, 2021, p. 9). It acts also like a pedagogy that allow the reproduction of MSM subcultures and communities of practices that express social meanings, pleasure seeking and risk taking behaviors, unsafety and ethics of care.…”
Section: Methodsmentioning
confidence: 99%
“…Chemsex is markedly different to such representations, because it is an action which is deemed 'risky' and a factor in the transmission of HIV, rather than the virus itself. Barrett (2017) draws attention to the fact that drug taking among GBTQ+ men has previously been discussed in different ways: as ubiquitous and problematic from a public-health perspective (similar to the discussion offered by Florêncio, 2021). However, Barrett (2017, pp.…”
Section: Sexuality and Healthcare Communicationmentioning
confidence: 99%
“…Typically, these studies use qualitative interviews with men who engage in chemsex (Ahmed et al, 2016;Hakim, 2019Hakim, , 2020Weatherburn et al, 2017). They have identified a sense of stigma associated with the practice (Pollard et al, 2018) as well as the perception that chemsex is a ubiquitous activity that is overly prevalent in queer communities (see Ahmed et al, 2016;Florêncio, 2021). Some studies have identified narratives associated with chemsexfor example, Milhet et al (2019) interviewed 33 men who engage in chemsex, finding that while their narratives focused on pleasure, relationship building, and sexual discovery, they simultaneously involved suffering and distress.…”
Section: Previous Studies On Chemsexmentioning
confidence: 99%
See 1 more Smart Citation